Blind Date with Antigone in Bohemia_CLONE - Volanakis, Adonis (My University, 2026)
Community engaged project, performance, exhibition, public intervention), curated by Lydia Matthews and Barbara Benish/ Art Mill, KINO Horazdovice, West Bohemia, Czech Republic.